2017
DOI: 10.5712/rbmfc12(39)1450
|View full text |Cite
|
Sign up to set email alerts
|

Doenças respiratórias em crianças e adolescentes: um perfil dos atendimentos na atenção primária em Vitória/ES

Abstract: Respiratory diseases in children and adolescents: profiling primary care visits in Vitória/ES Objetivo: Identificar as principais causas de atendimento por doenças respiratórias na atenção primária, em Vitória, ES, nos residentes de 0-19 anos, relacionando a gravidade das mesmas com idade e nível socioeconômico, e verificar a variação temporal de frequência desses atendimentos. Métodos: Estudo transversal descritivo dos atendimentos realizados em 2014 nas 30 unidades básicas de saúde do município de Vitória, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
1
0
10
Order By: Relevance
“…In their research, Botelho, Correia, Silva, Macedo and Silva (2003) indicate that environmental factors such as pollution of the air breathed and climate variations are determinant to increases in cases and gravity of ARIs in children below five. Corroborating with these data, a recent study by Frauches et al (2017) argues that most medical consultations due to respiratory diseases in the state of Espírito Santo/Brazil may be related to air quality in the city. Alves and Veríssimo (2006), in their turn, while investigating knowledge and practices related to ARIs in childhood, which included nursery school university employees, found that the most commonly mentioned causes for the onset of diseases were those relative to the environment, in addition to the child's individual susceptibility and lifestyle (pollution, weather, cigarettes, dust, emotional stress, and others).…”
Section: Discussionmentioning
confidence: 78%
“…In their research, Botelho, Correia, Silva, Macedo and Silva (2003) indicate that environmental factors such as pollution of the air breathed and climate variations are determinant to increases in cases and gravity of ARIs in children below five. Corroborating with these data, a recent study by Frauches et al (2017) argues that most medical consultations due to respiratory diseases in the state of Espírito Santo/Brazil may be related to air quality in the city. Alves and Veríssimo (2006), in their turn, while investigating knowledge and practices related to ARIs in childhood, which included nursery school university employees, found that the most commonly mentioned causes for the onset of diseases were those relative to the environment, in addition to the child's individual susceptibility and lifestyle (pollution, weather, cigarettes, dust, emotional stress, and others).…”
Section: Discussionmentioning
confidence: 78%
“…As condições sociais da população estão associadas ao processo de adoecer ou de morrer, quanto mais baixo o status social do indivíduo mais chance ele terá de ficar doente (Lindo, 2015). Estudos têm demonstrado que as vias aéreas são consideradas as principais regiões acometidas em crianças com uma condição socioeconômica menos favorável, dentre os principais agravos que podem ser citados é o desenvolvimento de infecções respiratórias, dado esse que corrobora com o presente estudo (Frauches, et al 2017).…”
Section: Resultsunclassified
“…As infecções respiratórias agudas são capazes de acometer as vias aéreas superiores, divididas em nariz, fossas nasais, seios perinasais, boca, faringe, laringe, estendendo-se ao ouvido médio, assim como as vias aéreas inferiores, sendo elas: traqueia, brônquios, bronquíolos e pulmões (FRAUCHES DO, et. al., 2017).…”
Section: Introductionunclassified